2015
DOI: 10.1016/j.beproc.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Transitive and anti-transitive emergent relations in pigeons: Support for a theory of stimulus-class formation

Abstract: Stimulus class formation is inferred when conditional discrimination training yields new (emergent) conditional relations between the training stimuli. The present experiments demonstrated two such relations in pigeons after successive matching-to-sample training. Experiment 1 showed that transitivity (AC matching) emerged after training on AB and BC arbitrary matching plus BB identity matching: Pigeons responded relatively more to the comparisons on AC test trials in which both the A samples and C comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
3
6
0
Order By: Relevance
“…In this experiment, we trained pigeons on a slightly different set of baseline relations vis-àvis those in Experiment 1 to test the theoretical prediction of "anti-reflexivity" (or emergent oddity): higher rates of responding in testing to nonmatching comparison stimuli than to matching comparison stimuli. If obtained, the results would complement previous findings and theoretical confirmations of antisymmetry (Urcuioli, 2008, Experiment 4) and antitransitivity (Urcuioli & Swisher, 2015).…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…In this experiment, we trained pigeons on a slightly different set of baseline relations vis-àvis those in Experiment 1 to test the theoretical prediction of "anti-reflexivity" (or emergent oddity): higher rates of responding in testing to nonmatching comparison stimuli than to matching comparison stimuli. If obtained, the results would complement previous findings and theoretical confirmations of antisymmetry (Urcuioli, 2008, Experiment 4) and antitransitivity (Urcuioli & Swisher, 2015).…”
Section: Methodssupporting
confidence: 86%
“…Our decision to train the controls on just two conditional discriminations (AB and BC) was based on the fact that the absence of AC matching task (which theoretically permits class merger in Groups R and O) should preclude reflexivity or antireflexivity (cf. Urcuioli & Swisher, , Experiment 2). Nonetheless, future research should equate the number of baseline relations across groups (3) to determine if the presence versus absence of reflexivity (or antireflexivity) is indeed a function of the nature of the third conditional discrimination (e.g., AC vs. CA).…”
Section: Discussionmentioning
confidence: 99%
“…Since the Urcuioli () study, Urcuioli and his colleagues have replicated both the symmetry and antisymmetry effects as well as demonstrated several additional emergent effects such as reflexivity and transitivity based on predictions of his hypothesis (Sweeney & Urcuioli, ; Swisher & Urcuioli, ; Urcuioli, ; Urcuioli & Swisher, ; ; Urcuioli & Swisher, ). In one recent study, Campos, Urcuioli and Swisher (2014) trained pigeons in a dual oddity task designed to produce class merger of the stimuli involved in arbitrary training in both sample and comparison positions.…”
mentioning
confidence: 93%
“…For Group DL, the average numbers of sessions to criterion were 8.8 for arbitrary matching, 15.3 for hue identity matching, and 10.5 for form identity matching. The numerical difference was statistically significant, F(2, 6) ¼ 13.92, most likely because the arbitrary and form identity tasks were familiar from the pigeons' previous experiences (Urcuioli & Swisher, 2015) whereas the hue identity task was new. For Group CL, the corresponding averages were 12.0, 14.5, and 13.8, respectively, which were not statistically different from one another, F(2, 6) ¼.26.…”
Section: Resultsmentioning
confidence: 95%
“…Recent studies using successive (go/no-go) matching-to-sample (MTS) have shown reliable evidence for associative symmetry and other emergent relations of equivalence in pigeons (e.g., Campos, Urcuioli & Swisher, 2014;Frank & Wasserman, 2005;Sweeney & Urcuioli, 2010;Urcuioli, 2008;Urcuioli & Swisher, 2015). The positive symmetry results, in particular, stand in stark contrast to the mostly negative findings previously obtained in studies using two-alternative MTS (e.g., Dugdale & Lowe, 2000;Hogan & Zentall, 1977;Lionello-DeNolf & Urcuioli, 2002;Sidman, Rauzin, Lazar, Cunningham, Tailby & Carrigan, 1982; see also Lionello-DeNolf, 2009 andUrcuioli, 2015).…”
mentioning
confidence: 98%